2007
DOI: 10.1186/1471-2164-8-440
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide changes in expression profile of murine endogenous retroviruses (MuERVs) in distant organs after burn injury

Abstract: Background: Previous studies have shown that burn-elicited stress signals alter expression of certain murine endogenous retroviruses (MuERVs) in distant organs of mice. These findings suggest that MuERVs may participate in a network of pathophysiologic events during post-burn systemic response. To gain a better understanding of the biological roles of MuERVs in post-burn systemic response, we examined the genome-wide changes in the MuERV expression profiles in distant organs and the biological properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Data from our laboratory reveal that a substantial number of full-length MuERVs (MuLV-type) with intact coding potentials for all three essential polypeptides are likely to be involved in postburn injury response (8). Interestingly, we observed that treatment of control no-burn animals with anesthetic agents (isoflurane and ketamine/xylazine) alone followed by resuscitation with saline and narcotics affects the expression of certain MuERVs (8).…”
Section: Micementioning
confidence: 83%
See 1 more Smart Citation
“…Data from our laboratory reveal that a substantial number of full-length MuERVs (MuLV-type) with intact coding potentials for all three essential polypeptides are likely to be involved in postburn injury response (8). Interestingly, we observed that treatment of control no-burn animals with anesthetic agents (isoflurane and ketamine/xylazine) alone followed by resuscitation with saline and narcotics affects the expression of certain MuERVs (8).…”
Section: Micementioning
confidence: 83%
“…Interestingly, we observed that treatment of control no-burn animals with anesthetic agents (isoflurane and ketamine/xylazine) alone followed by resuscitation with saline and narcotics affects the expression of certain MuERVs (8). Murine leukemia viruses have been regarded as simple retroviruses because their coding potentials are reported to be limited only to three essential polypeptides in conjunction with their splicing potentials.…”
Section: Micementioning
confidence: 99%
“…However, it has been reported that some other MuERV families, such as MLV type-ERVs and MMTV type-ERVs, were expressed in mice under both normal and stress conditions in a tissue specific manner (Lee et al 2007; Cho et al 2008; Lee et al 2011). In this experiment, the expression of MDL-ERVs was examined in seven different tissues (brain, heart, kidney, liver, lung, spleen, and thymus) of 12 week-old C57BL/6J female mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have suggested that ERVs and their gene products participate in a range of pathobiologic processes in humans and animals, such as placental morphogenesis, neuronal degeneration, response to injury, and inflammation (Harris 1998); Christensen 2005; Lee et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Genomic sequences dedicated to conventional protein-coding genes only comprise ~3 % of the human genome while HERVs and related elements make up ~8 % (Lander et al, 2001; Venter et al, 2001). Our recent findings that burn-incited stressors differentially activate ERVs in mice and that some murine ERV gene products harbor pro-inflammatory potential led us to investigate HERV responses in burn patients (Kwon et al, 2009; Lee et al, 2007; Lee et al, 2011; Lee et al, 2008). It is possible that HERVs and other human genomic elements, such as small interspersed nuclear elements (SINEs) and long interspersed nuclear elements (LINEs), could also participate in burn-elicited pathologic events.…”
Section: Discussionmentioning
confidence: 99%